Analisis Pendapatan Terhadap Karakteristik Usahatani Integrasi Tanaman Perkebunan-Sapi: Kasus di Desa Mesa, Kabupaten Maluku Tengah - Agung Budi Santoso (Institut Pertanian Bogor, 2017)
Crop-livestock was a concept of zero waste system and good for the environment. This study aimed to determine the effect of farming characteristics on farmer incomes Mesa Village, Teon Nila Serua Sub District, Central Maluku District. Type of farming characteristics consisted of two groups, namely farmers who have integrated coconut, cocoa and cattle, and farmers who relied on the plantation sector. The data used was primary data obtained by the method of interviews and questionnaires. Data were analyzed using the Mann-Whitney test statistic. The results obtained that the income of farmers who perform the integration of cattle, coconuts, and cocoa did not differ significantly with farmers' income derived from the coconut and cocoa. This was because maintenance of cattle still traditionally and there has been no development of farm products. Increased productivity in the crop-livestock system could be done by making a communal cage, cultivation of fodder crops, and dissemination of technology